ANALISIS PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN INFRASTRUKTUR DI DESA KARANGWOTAN KECAMATAN PUCAKWANGI KABUPATEN PATI - Ajib Mahendra; , Maesaroh , Maesaroh; Nina Widowati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
Changes in an increasingly advanced era require optimal development to be able to keep up with changing times. The development aims to realize people's welfare which is one of the goals of the Unitary State of the Republic of Indonesia. Decentralization makes it easy for each region to be able to carry out development based on the potential possessed by a region. However, infrastructure development in Karangwotan Village has not run optimally. This is due to the lack of community participation in infrastructure development in their area. Lack of community participation has an impact on infrastructure development that is not by community needs. This study aims to determine and analyze community participation in infrastructure development in Karangwotan Village, Pucakwangi District, Pati Regency, the inhibiting factors, and the driving factors for community participation in infrastructure development. This research uses a descriptive qualitative approach. Data collection techniques through observation, interviews, and documentation. The results of the analysis and discussion in this study indicate that community participation in Karangwotan Village has not run optimally. This problem is caused by factors inhibiting participation such as a lack of public awareness in attending development planning activities (MUSRENBANGDes) and a lack of outreach by the government regarding the importance of community participation in infrastructure development. There are also factors driving community participation in development such as the opportunity to participate, the willingness to participate, and the ability to participate in the implementation of infrastructure development. Suggestions or recommendations in this study are to increase socialization carried out by the government to the community so that they understand the importance of their participation in infrastructure development in their area.